The reflector - Battaglia, Jennifer; Shaw, Margie Hodges; Daiss, Susan; Gdowski, Martha (Meliora Press, an imprint of the University of Rochester Press, 2021)
"The Reflector is a humanities-based companion to the medical school's scientific dissection manual. The authors (Jennifer Battaglia, Margie Hodges Shaw, Susan Daiss, and Martha Gdowski) say The Reflector resonates fully with the biopsychosocial values central to the University's medical school. The publication encourages the students to think more broadly about the cultural, political, legal, ethical and personal issues connected to dissection. Says Gdowski in the preface: "You will never know your donor in the way you may know the lab partners with whom you share this dissection experience. ... Yet, you will come to know them in a memorable way." Although it not required reading, it appears that a majority of medical students opt to read it (online) and find it useful"--